Simultaneous Estimation of Drotaverine HCl and Mefenamic Acid in Tablet Dosage Form Using Spectrophotometric Method - ROOSEWELT, C.; HARIHRISHNAN, N.; GUNASEKARAN, V.; CHANDRASEKARAN, S.; HARIBASKAR, V.; PRATHAP, B. (Asian Journal of Chemistry, 2010)
A simple, fast an precise simultaneous estimation method using Vierodt's method has been developed for the simultaneous determination of drotaverine HCl and mefenamic acid in pure and combined tablet dosage forms. Shimadzu UV-1700 instrument was used and the λmax of drotaverine HCl and mefenamic acid was found to be 228 and 288 nm, respectively using methanol and 0.01 M sodium hydroxide in the ratio of 9:1. Drotaverine HCl and mefenamic acid were found to be linear in the concentration range of 2-12 μg/mL and 4-24 μg/mL, respectively at their respective wavelengths. Amount found for drotaverine HCl and mefenamic acid was found to be 80.08 and 250.79 mg/tablet, respectively. Percentage recovery range was found to be within 99.9-100.3 % for drotaverine HCl and 99.80-100.08 % for mefenamic acid. The percentage RSD was found to be lower than 2 % proves that the method is precise. The application of simultaneous equation method by UV spectroscopy can be employed for the estimation of drotaverine HCl and mefenamic acid for routine analysis for a combination containing these two components in pure and tablet dosage forms.